Development of a non-radioactive probe generated by RAPD-PCR for the detection of Theileria annulata - SARAVANAN, B C; BANSAL, G C; MANIGANDAN, L; SANKAR, M; RAVINDRAN, R; RAO, J R (The Indian Journal of Animal Sciences, 2011)
A highly reproducible, dominant and monomorphic fragment of 963 base pair (bp) was amplified from the genome of Theileria annulata by random amplified polymorphic DNA - polymerase chain reaction (RAPD-PCR) using a arbitrarily selected primer APâ‚â‚‡ (5â€™-GGTGACGCAG-3â€™). This fragment was reamplified using the same random primer (APâ‚â‚‡), gel purified and labeled with digoxigenin (DIG). Dot-blot hybridization of total genomic DNA with the probe detected Parbhani and Izatnagar strains of T. annulata with a threshold detection level of 10 pg of parasite template DNA. No cross-hybridization was observed with Babesia bigemina, Trypanosoma evansi and the bovine host DNA. The sensitivity of the DIG labeled probe developed in this study is at least 6 to 65 times higher than the other DIG labeled probes developed in India and therefore considered highly suitable for diagnosis of carrier animals especially when they are imported or exported from the country.